Interface Stresses Due to Imbalanced Diffusion in Wirebonding Between Gold (Au) and Aluminum (Al) - Anita Akmar Kamarolzaman; Ghazali Omar; Fina Sofiyyah Shukor (Bumi Publikasi Nusantara, 2026)
Wirebonding is a fundamental process in semiconductor manufacturing, essential for creating reliable electrical connections between integrated circuits and their packaging. This paper explores the complexities of interface stresses arising from solid-state diffusion during wirebonding, with particular attention to the interactions between gold (Au) wires and aluminum (Al) bond pads. Due to the different diffusion rates of Au and Al atoms, intermetallic compounds (IMCs) form at the interface, playing a critical role in bond integrity. However, the growth of these IMCs also generates significant mechanical stresses, which can compromise the reliability and lifespan of wirebonded connections. Through detailed experimental analysis, this study investigates the kinetics of IMC growth, the influence of activation energy on diffusion, and the resulting microstructural evolution at bonded interfaces. By clarifying the mechanisms driving IMC formation and associated stresses, the paper offers insights into optimizing wirebonding processes. These include the selection of suitable bonding parameters and materials to reduce stress and enhance the performance and durability of semiconductor devices. Ultimately, the findings support the advancement of wirebonding techniques aimed at improving the reliability and efficiency of semiconductor packaging.